Finanças pessoais: um estudo com os colaboradores de uma cooperativa médica - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This study has the objective to verify how the workers of a medical cooperative, situated at the county of Santa do Livramento, govern their personal finances. Due to the necessity to comprehend the existing theory of personal finances, this study is structured in the following way: personal finances e educational finances, personal financial planning and domestic budget. The research developed by the way of study, with a research of descriptive character, with a quantitative bias, utilizing a questionnaire as an instrument to collect data. The data analysis was made with the descriptive statistic technique. It was noticed interest by the majority of the participants for the subject. The variables like age, scholarship and income can influence in the decision process on the act of when to save or spend money. It is given great importance to the practice of planning, however some people find it difficult due to how they do not know how to do it, those that know about the subject, for the most part develop it by themselves.
Keywords: Administração; Finanças pessoais; Educação financeira; Orçamento pessoal; Personal finances; Financial education; CNPQ::CIENCIAS SOCIAIS APLICADAS